Investigating the efficacy of baricitinib in new onset type 1 diabetes mellitus (BANDIT)—study protocol for a phase 2, randomized, placebo controlled trial - M. Waibel; H. E. Thomas; J. M. Wentworth; J. J. Couper; R. J. MacIsaac; F. J. Cameron; M. So; B. Krishnamurthy; M. C. Doyle; T. W. Kay (Trials, 2022)
Abstract Background Type 1 diabetes (T1D) places an extraordinary burden on individuals and their families, as well as on the healthcare system. Despite recent advances in glucose sensors and insulin pump technology, only a minority of patients meet their glucose targets and face the risk of both acute and long-term complications, some of which are life-threatening. The JAK-STAT pathway is critical for the immune-mediated pancreatic beta cell destruction in T1D. Our pre-clinical data show that inhibitors of JAK1/JAK2 prevent diabetes and reverse newly diagnosed diabetes in the T1D non-obese diabetic mouse model. The goal of this study is to determine if the JAK1/JAK2 inhibitor baricitinib impairs type 1 diabetes autoimmunity and preserves beta cell function. Methods This will be as a multicentre, two-arm, double-blind, placebo-controlled randomized trial in individuals aged 10–30 years with recent-onset T1D. Eighty-three participants will be randomized in a 2:1 ratio within 100 days of diagnosis to receive either baricitinib 4mg/day or placebo for 48 weeks and then monitored for a further 48 weeks after stopping study drug. The primary outcome is the plasma C-peptide 2h area under the curve following ingestion of a mixed meal. Secondary outcomes include HbA1c, insulin dose, continuous glucose profile and adverse events. Mechanistic assessments will characterize general and diabetes-specific immune responses. Discussion This study will determine if baricitinib slows the progressive, immune-mediated loss of beta cell function that occurs after clinical presentation of T1D. Preservation of beta cell function would be expected to improve glucose control and prevent diabetes complications, and justify additional trials of baricitinib combined with other therapies and of its use in at-risk populations to prevent T1D. Trial registration ANZCTR ACTRN12620000239965 . Registered on 26 February 2020. ClinicalTrials.gov NCT04774224. Registered on 01 March 2021